Malor positioned thoracic drains diagnosed by image examination (Research, Society and Development, 2021)
Thoracic drainage is a method whereby substances are removed through a drain, whether bloody as in a hemothorax, or air, in the case of pneumothorax, so that it is possible to slide between the pleura and maintain an adequate pulmonary expansion. In the case of patients who have had poor insertion of the drain into the pleural cavity, there may be a worsening of the clinical picture, with reduced ventilation, respiratory failure, occurrence of infections, or even iatrogenic pneumothorax. Objective: To analyze the imaging findings of poorly positioned chest drains on computed tomography. Materials and methods: This research is a retrospective, quantitative study with a descriptive focus, in which data from computed tomography exams provided by the Polimagem Radiodiagnóstico clinic in the municipality of Marabá-PA were used. Results: In the present study, the group with the highest incidence of complications related to inadequate drain placement was male, between 19 and 59 years old, indicated by traumatic causes, the most common location for the insertion of the incorrect drain occurred in the intraparenchymal region causing main complications are pneumothorax, bleeding and in more advanced cases the appearance of fistulas. Conclusion: The findings of the imaging examination were essential for detecting iatrogenesis caused by poorly inserted drains, the results should be expanded to avoid inadequate drain placement, also adopting standardized hospital protocols and training of the health team to use them.